2013
DOI: 10.1002/mds.25319
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine consumption and risk of dyskinesia in CALMPD

Abstract: Background Adenosine A2A receptor antagonists reduce or prevent the development of dyskinesia in animal models of levodopa-induced dyskinesia. Methods We examined the association between self-reported intake of the A2A receptor antagonist caffeine and time to dyskinesia in the Comparison of the Agonist Pramipexole with Levodopa on Motor Complications of Parkinson’s Disease (CALM-PD) and CALM Cohort extension studies, using a Cox proportional hazards model adjusting for age, baseline Parkinson’s severity, sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
3
33
4
1
Order By: Relevance
“…To examine the association between baseline PET data and time to onset of wearing-off, LID, and any motor complication (wearing-off/dyskinesia), we used a Cox proportional hazards model, which was adjusted for relevant covariates. Similar to previous studies, 6,21,22 sex, age at symptom onset, disease duration at baseline, baseline UPDRS ADL and motor scores, baseline weight, treatment allocation (initial randomization to cabergoline/levodopa), and antiparkinsonian therapy at time of motor complication onset (antiparkinsonian agents, levodopa LED) were entered as covariates into this model. A stepwise selection process, with significance levels for both entry and retention in the model set at 0.05, was used to select the most significant predictors.…”
mentioning
confidence: 99%
“…To examine the association between baseline PET data and time to onset of wearing-off, LID, and any motor complication (wearing-off/dyskinesia), we used a Cox proportional hazards model, which was adjusted for relevant covariates. Similar to previous studies, 6,21,22 sex, age at symptom onset, disease duration at baseline, baseline UPDRS ADL and motor scores, baseline weight, treatment allocation (initial randomization to cabergoline/levodopa), and antiparkinsonian therapy at time of motor complication onset (antiparkinsonian agents, levodopa LED) were entered as covariates into this model. A stepwise selection process, with significance levels for both entry and retention in the model set at 0.05, was used to select the most significant predictors.…”
mentioning
confidence: 99%
“…Nevertheless, the adenosine A2A receptor antagonism attributed to YM caffeine could be the best explanation for the protective role of YM in the risk of PD [9,37,38]. An extensive review of the literature supports the potential neuroprotective and pharmacological effects of caffeine mediated by A2A receptor antagonism.…”
Section: Discussionmentioning
confidence: 89%
“…Caffeine has attracted considerable attention in the management of nonmotor symptoms of PD that do not improve with the current DAergic drugs (Prediger, 2010). Accordingly, in a 6-week randomized placebo-controlled clinical trial, caffeine per se improved motor functions in PD patients (Postuma et al, 2012) and was also reported to reduce the risk of dyskinesia in PD patients receiving DAergic agents (Wills et al, 2013).…”
Section: Discussionmentioning
confidence: 99%